(untitled) (Research, Society and Development, 2021)
The effluents from carbonization or pyrolysis and wood charcoal have aggregated thermal energy and, in conventional charcoal kilns, part of the wood is burned to ignite the burning in the kilns and the effluents generated are dispensed in the atmosphere and in the soil, which causes energy losses and environmental pollution. In this study we seek a clean and sustainable alternative to produce energy, in addition to the search for a system with satisfactory performance in the generation of electric energy. The objective of this study was to evaluate how much electricity can be produced from wood carbonization effluents by ONDATEC technology, using the Brayton and Rankine cycle, also known as Combined Cycle. This method presents a high power generation efficiency, around 50%, compared to other generation systems. A field experiment was carried out from October 21st to 24th, 2010 to determine the calorific value of wood carbonization effluents, using a microwave oven, (condensable and non-condensable gas), in the city of Uberaba -Mg, Brazil. The data generated in this study reveals important information for companies looking for a way to produce clean and renewable electricity from reforestation wood, in addition to the effort to minimize environmental pollution, ensure sustainability in production systems and the growing search for new sources of energy. A complete description of the experiment, including details of the project, is presented in this work.